2013
DOI: 10.1038/mt.2013.57
|View full text |Cite
|
Sign up to set email alerts
|

Gene Silencing via RNAi and siRNA Quantification in Tumor Tissue Using MEND, a Liposomal siRNA Delivery System

Abstract: Small interfering RNA (siRNA) would be predicted to function as a cancer drug, but an efficient siRNA delivery system is required for clinical development. To address this issue, we developed a liposomal siRNA carrier, a multifunctional envelope-type nanodevice (MEND). We previously reported that a MEND composed of a pH-sensitive cationic lipid, YSK05, showed significant knockdown in both in vitro and in tumor tissue by intratumoral injection. Here, we report on the development of an in vivo siRNA delivery sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(114 citation statements)
references
References 35 publications
1
112
0
1
Order By: Relevance
“…5 mol%) was sufficient for YSK05-MEND to circulate in the blood, unlike cationic doTAP-MENd. 124) This suggests that ySK05-MENd is a promising system for use in the in vivo delivery of nucleic acids to tumors. As another type of pH-sensitive lipid, we reported SS-cleavable protonactivated lipid-like material (ssPalm), which contains two tertiary amines that are positively charged at acidic pH and a disulfide bond that can be cleaved in a reducing environment.…”
Section: )mentioning
confidence: 99%
“…5 mol%) was sufficient for YSK05-MEND to circulate in the blood, unlike cationic doTAP-MENd. 124) This suggests that ySK05-MENd is a promising system for use in the in vivo delivery of nucleic acids to tumors. As another type of pH-sensitive lipid, we reported SS-cleavable protonactivated lipid-like material (ssPalm), which contains two tertiary amines that are positively charged at acidic pH and a disulfide bond that can be cleaved in a reducing environment.…”
Section: )mentioning
confidence: 99%
“…YSK-MENDs were prepared as previously reported [10,11]. Briefly, 1,500 nmol of YSK05, 750 nmol of POPE, 750 nmol chol and 150 nmol PEG-DMG were dissolved in 400 μL of 90% (v/v) aqueous tertiary butanol (t-BuOH).…”
Section: Mend Preparationmentioning
confidence: 99%
“…5' RACE-PCR for the detection of Cd31 mRNA cleaved by si-Cd31 was carried out as previously reported [11]. Briefly, GeneRacer Adaptor was ligated into cleaved Cd31 mRNA, and then reverse transcribed with Cd31 Gene Specific Primer by SuperScript III (Invitrogen).…”
Section: Confirmation Of Rnai-mediated Gene Silencing By 5' Race-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…We developed a tumor-targeting siRNA delivery system via the enhanced permeability and retention (EPR) effect, which involves the passive accumulation of a long-circulating macromolecule in tumor tissue [38]. We reported that the PEGylated YSK05-MEND retained encapsulated siRNA intact in the circulation and PEGylated YSK05-MEND suppressed a cancer-related gene via RNAi-mediated silencing using 5' rapid amplification and cDNA ends (5'-RACE)-PCR [39]. Likewise, the liver can be targeted by passive accumulation because neutral liposomes can accumulate in the liver through the fenestrae of liver endothelial cells and can be internalized into hepatocytes via a low density lipoprotein receptor through absorption of apolipoprotein E in the bloodstream [40].…”
Section: Sirna Delivery To Tumors and The Tumor Vasculature Using A Pmentioning
confidence: 99%